2017
DOI: 10.3390/molecules22050849
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effects of Tea

Abstract: Diabetes mellitus (DM) is a chronic endocrine disease resulted from insulin secretory defect or insulin resistance and it is a leading cause of death around the world. The care of DM patients consumes a huge budget due to the high frequency of consultations and long hospitalizations, making DM a serious threat to both human health and global economies. Tea contains abundant polyphenols and caffeine which showed antidiabetic activity, so the development of antidiabetic medications from tea and its extracts is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 143 publications
(164 reference statements)
2
58
0
1
Order By: Relevance
“…It has been seen that treatment with GTE powder brought down FBGL from a higher value on the 14 th day. The results are in agreement with the other worker 18 .…”
Section: Discussionsupporting
confidence: 93%
“…It has been seen that treatment with GTE powder brought down FBGL from a higher value on the 14 th day. The results are in agreement with the other worker 18 .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, experimental studies have discovered that several bioactive components, including catechins, gallic acid, polysaccharides and epigallocatechin-3-gallate, within tea show antioxidant activity (28,29) and improve insulin sensitivity (30) . The polysaccharides extracted from fully fermented black tea and dark tea contain a higher percentage of low molecular weight portions (antioxidants) than those extracted from green tea and oolong tea, resulting in more benefits to T2DM (9) . According to Bhupathiraju et al, the effect of tea on diabetes might be attributed to caffeine.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant bioactive substance contained in tea, for example, catechin, caffeine, thearubigins and polyphenols, has been suggested to have anti-diabetic effects in diabetic mice (9) . In addition, researches (10,11) reported that tea consumption could prevent the development of obesity, T2DM and cancer.…”
mentioning
confidence: 99%
“…It was reported that there were nearly 4000 bioactive compounds in tea and one third was contributed by polyphenols [2,3]. Studies have shown that drinking teas can prevent cancer [4], alleviate oxidative stress, and suppress hyperglycemia and antidiabetic effect [5].…”
Section: Introductionmentioning
confidence: 99%